Biodegradable poly (lactic acid)clay nanocomposite by melt intercalation :a study of mechanical properties - Nasobah, Ahmad (2010)
Polymer nanocomposites have highly improvement in mechanical properties compared to conventional polymer.In this project, polylactic acid was reinforced with the organoclay (Cloisite 20A) as nanofiller by using twin screw extruder at 210⁰C and 100 rpm.Fourier Transform Infrared Spectroscopy(FT-IR)was used to identify the attendance of nanoparticle in polymer matrix.The mechanical properties were evaluated by measuring their tensile stress,Modulus Young’s and hardness.In FT-IR results,PLA/C20A nanocomposite shows the peak between 1580 cm -1 and 1610 cm-1 which is representing amine group of Cloisite 20A.However,in pure polylactic acid matrix the peak is absent.Mechanical studies indicate that a significant increasing by 70.5% in tensile stress and 394.3% in Modulus Young’s shows in PLA/1 wt.% C20A.It is expected because this behaviour is mainly due to high stiffness and modulus of nanoclay that reinforce the blend matrix.Further,PLA/ 1 wt. % C20A also give the high increasing by 3.23% in hardness testing because the strong interfacial interaction between nanofiller and polymer matrix.As a conclusion,an addition of Cloisite 20A significantly improves mechanical properties of polylactic acid matrix and PLA/ 1 wt.% C20A had the higher increasing in tensile strength,Modulus Young’s and hardness.